Peran Domestik-Publik Prajurit Kowad Korem 072/Pamungkas Yogyakarta - Abqori, Najih (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2022)
: This research aims to examine the role of the domestic-public Komando Wanita Angkatan Darat (Kowad). In this case, the role in question is: first, the role of women as Kowad (public role). Second, as a wife to meet the needs of her husband, as the mother of their children and as a housewife (domestic role). Third, as a member of society who must be responsive to social problems. The sample used is 8 respondents, who is a member of Kowad Sub Koor Yogyakarta which are located in Magelang, Temanggung and Yogyakarta. This research is a type of field research with qualitative and descriptive-analytical methods. Collect data by interviewing directly with informants. The results of this research indicate that the function of each family member in Kowad Sub Koor Yogyakarta is husband making a living (public role), wife doing housework (domestic task) and the task of the child is to study (school). There are three forms of roles in the division of domestic tasks: 1) balanced division of labor, 2) wife's job is tougher, 3) division of labor with an autonomous system. The fact shows that the division of labor is heavier on the wife is more dominant. The type of family Kowad Sub Koor Yogyakarta included in the type of traditional family, because in general there is no balance of roles between husband and wife.